Mensa Guide to Chess : 30 Days to Great Chess - Hochberg, Burt; Foreword By Bruce Pandolfini (New Delhi Goodwill Publishing House, 2009)
Learn how to win at chess in just 30 days. It's a game of logic and common sense, something that we all can tap into. What you need is the guidance of an expert, who makes it easy to understand and follow the moves and rules, as well as the tactics and the strategies that will give you the edge over your competitors. Engaging explanation, example and review quizzes that let you approach each position as if it were an actual game position as if it were an actual game enable you to succeed.
Includes Index.
Keywords: Chess